Building Design In Virtual Reality Modelling - Mr. S. Azhagarsamy; S. Akshay; R. Ashwin Kumar; K. Lokesh; P. Mithun (International Journal of Scientific Research in Civil Engineering, 2022)
As immersive Virtual Environment (VE) applications get more complicated, it’s evident that we’ll require a solid grasp of VE Interaction concepts. Designers, in particular, need assistance in selecting three-dimensional interaction strategies. As a result, we provide a systematic testbed evaluation strategy for VE interaction strategies. A technique for establishing a virtual workspace is presented, as well as the philosophy and approach for generating a workspace that can be seen via a VR head-mounted device. This technique creates a BIM-based design prototype system that allows for realistic visualisation of building and lighting conditions. The residential building is designed with the help of Autodesk Revit Architecture software. To enliven the virtual Scene, these models are loaded into Unity Engine. The simulation’s findings may be seen and interacted with using a virtual reality controller. For the virtual reality controller, a microunit controller with a communication interface that includes mechanical physical limit feedback is being created. Between virtual reality sequences, the integrated C# script design inside the unity game engine plays a significant role. The navigation and GUI are made using unity and a C# script. In order to move and grab the pieces, the animation may be created in modelling software and the attributes of the elements existent in the Virtual Space are added to Unity.